PERTUMBUHAN MISELIUM JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA MEDIA DASAR LIMBAH KULIT SINGKONG - umrah umrah; Asriani Hasanuddin; Eny Yuniati; Trismansyah Trismansyah (Biology Department, Mathematics and natural science, Tadulako University, 2023)
Cassava peel used as the basic medium for the growth of mycelium of white oyster mushroom (Pleurotus ostreatus). The purpose of this study : to determine the growth of white oyster mushroom mycelium (P. ostreatus) and to determine the ratio of basic media that can provide the best growth of white oyster mushroom mycelium. This study was designed in a completely randomized design (CRD) consisting of seven treatments and three replications, namely P1 (100% cassava peel base medium), P2 (MD 80% + SG 20%), P3 (MD 60% + SG 40% ), P4 (MD 40% + SG 60%), P5 (MD 80% + SG 10%), P6 (SG 100%), P7 (70% sawdust, 20% rice bran + 10% corn flour). The results of observation this research of the fastest growth at P4, P5 and the lowest at P6, were seen from the observation of mycelium growth. Colony stages on Potato Sucrose Agar (PSA) media, the results obtained were the highest number of colonies (CFU) in P1 treatment 1.83 x 1012 CFU/g and the lowest in P6 treatment 0.8 x 1012 CFU/g. The fastest storage time in treatment P4, P5 and the lowest in treatment P6.